Fractional Anisotropy of the Fornix and Hippocampal Atrophy in Alzheimer’s Disease - Kantarci, Kejal (Frontiers in Aging Neuroscience, 2014)
Decrease in the directionality of water diffusion measured with fractional anisotropy on diffusion tensor imaging has been linked to loss of myelin and axons in the white matter. Fornix fractional anisotropy is consistently decreased in patients with mild cognitive impairment and Alzheimer’s disease. Furthermore, decreased fornix fractional anisotropy is one of the earliest MRI abnormalities observed in cognitively normal individuals who are at an increased risk for Alzheimer’s disease, such as in pre-symptomatic carriers of familial Alzheimer’s disease mutations and in pre-clinical Alzheimer’s disease. Reductions of fractional anisotropy at these early stages which predicted the decline in memory function. Fornix carries the efferent projections from the CA1 and CA3 pyramidal neurons of the hippocampus and subiculum, connecting these structures to the septal nuclei, anterior thalamic nucleus, mammillary bodies and medial hypothalamus. Fornix also carries the afferent cholinergic and GABAergic projections from the medial septal nuclei and the adjacent diagonal band back to the medial temporal lobe, interconnecting the core limbic structures. Because fornix carries the axons projecting from the hippocampus, integrity of the fornix is in-part linked to the integrity of the hippocampus. In keeping with that, fornix fractional anisotropy is reduced in subjects with hippocampal atrophy, correlating with memory function. The literature on fractional anisotropy reductions in the fornix in the clinical spectrum of Alzheimer’s disease from pre-symptomatic carriers of familial Alzheimer’s disease mutations to pre-clinical Alzheimer’s disease, mild cognitive impairment and dementia stages is reviewed.